Analisis Performa dari Algoritma Kriptografi RSA dan ElGamal dalam Enkripsi dan Dekripsi Pesan - Fajrin, Ahmad Miftah; Benedict, Jeremy Richard; Kusuma, Henri Jayanata (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Cryptography is one of the most important things in computer science because it is related to data security or message security. Cryptographic algorithms are used to secure a message, the most popular of which are the Rivest-Shamir-Adleman (RSA) and ElGamal algorithms. ElGamal employs a prime number modulo while RSA employs the factorial of two large integer numbers. The workings of these two algorithms are distinct, and each has distinct advantages. Even though the two algorithms use different processes, they can both encrypt and decrypt a message. There are speed factors of execution time and peak memory when running the encryption and decryption process. One of these two factors is hardware, which determines the environment that will be used. According to the findings of this study, the RSA algorithm has a faster execution time than ElGamal. In terms of peak memory, both algorithms get the result similarly, with the same peak memory results shown..